2002
DOI: 10.1128/iai.70.7.3856-3864.2002
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Bovine Paratuberculosis Is Associated with Local Loss of CD4+T Cells, Increased Frequency of γδ T Cells, and Related Changes in T-Cell Function

Abstract: Bovine paratuberculosis is caused by the infection of young calves with Mycobacterium avium subsp. paratuberculosis, resulting in a chronic granulomatous infection of predominantly the ileum. After an incubation period of 2 to 5 years, the disease becomes progressive in some of the chronically infected, but asymptomatic cows. This results in a protein-losing enteropathy that will ultimately be fatal. A loss of cell-mediated immune responses in symptomatic animals has been described, but no information is avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 38 publications
9
79
2
4
Order By: Relevance
“…The PMBC had been obtained from whole blood by density gradient centrifugation as published previously (Koets et al, 2002). The DNA from purified PBMC or whole blood was isolated using the DNAWizard-Kit (Promega, Madison, WI, USA) according to manufacturer's instructions and spectrophotometrically tested for yield and purity.…”
Section: Preparation Of Genomic Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The PMBC had been obtained from whole blood by density gradient centrifugation as published previously (Koets et al, 2002). The DNA from purified PBMC or whole blood was isolated using the DNAWizard-Kit (Promega, Madison, WI, USA) according to manufacturer's instructions and spectrophotometrically tested for yield and purity.…”
Section: Preparation Of Genomic Dnamentioning
confidence: 99%
“…In these later phases, the Th1 CMI declines to an undetectable low level and the amount of apparently non-protective antibodies increases. The loss of protective CMI leads to a widely disseminated infection and uncontrolled growth of mycobacteria in macrophages, causing the clinical manifestation of paratuberculosis (Koets et al, 2002). Hence, following a prolonged period of chronic diarrhoea, weight loss and decreased milk production, cows become emaciated and may die from this protein-loosing enteropathy (Coussens, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The differences between normal and infected animals in responses to T lymphocytes were studied by Bassey and Collins (1997) who demonstrated that the major subpopulation producing IFN-γ are CD4 + lymphocytes, and that, in the animals affected by paratuberculosis, the effect of γδ T lymphocytes is not mediated through the production of IFN-γ. Koets et al (2002) demonstrated a significant decrease in CD4 + T-cell frequency and a significant increase in TcR-N12 + gamma delta T-cell frequency in illeum lamina propria lymphocytes of symptomatic animals compared to the asymptomatic shedders. These authors also demonstrated shi� of the immune reaction from Th1 type towards the Th2 type at the time of the development of clinical signs (Koets et al, 1999(Koets et al, , 2001.…”
Section: Original Papermentioning
confidence: 99%
“…IFN-g production by TH1-cells are, therefore, major mediators of specific immunity during early infection (Stabel 2000). Peripheral and intestinal CMI responses are reduced in symptomatic compared to asymptomatic animals (Koets et al 2002). Disease development appears to be linked with local loss of CD4 C T-cells and gd T-cells (Chiodini 1996;Koets et al 2002).…”
Section: Immune-based Test Platformsmentioning
confidence: 99%
“…Peripheral and intestinal CMI responses are reduced in symptomatic compared to asymptomatic animals (Koets et al 2002). Disease development appears to be linked with local loss of CD4 C T-cells and gd T-cells (Chiodini 1996;Koets et al 2002). The fundamental defect that could be connected with a reduction in CMI response is the deregulation in MAP-mediated macrophage function (Tooker et al 2002;Weiss et al 2002;Zur et al 2003).…”
Section: Immune-based Test Platformsmentioning
confidence: 99%